Immuno‐miRs: critical regulators of T‐cell development, function and ageing. Issue 1 (January 2015) - Kroesen, Bart‐Jan; Teteloshvili, Nato; Smigielska‐Czepiel, Katarzyna; Brouwer, Elisabeth; Boots, Anne Mieke H.; van den Berg, Anke; Kluiver, Joost
Summary MicroRNAs (miRNAs) are instrumental to many aspects of immunity, including various levels of T‐cell immunity. Over the last decade, crucial immune functions were shown to be regulated by specific miRNAs. These 'immuno‐miRs' regulate generic cell biological processes in T cells, such as proliferation and apoptosis, as well as a number of T‐cell‐specific features that are fundamental to the development, differentiation and function of T cells. In this review, we give an overview of the current literature with respect to the role of miRNAs at various stages of T‐cell development, maturation, differentiation, activation and ageing. Little is known about the involvement of miRNAs in thymic T‐cell development, although miR‐181a and miR‐150 have been implicated herein. In contrast, several broadly expressed miRNAs including miR‐21, miR‐155 and miR‐17~92, have now been shown to regulate T‐cell activation. Other miRNAs, including miR‐146a, show a more T‐cell‐subset‐specific expression pattern and are involved in the regulation of processes unique to that specific T‐cell subset. Importantly, differences in the miRNA target gene repertoires of different T‐cell subsets allow similar miRNAs to control different T‐cell‐subset‐specific functions. Interestingly, several of the here described immuno‐miRs have also been implicated in T‐cell ageing and there are clear indications for causal involvement of miRNAs in immunosenescence. It is concluded that immuno‐miRs have a dynamic regulatory role in many aspects of T‐cell differentiation, activation, function and ageing. An important notion when studying miRNAs in relation to T‐cell biology is that specific immuno‐miRs may have quite unrelated functions in closely related T‐cell subsets.